Peran Strategi Pemasaran, Pelayanan dan Kualitas Produk Minyak Kayu Putih Cap Dragon terhadap Minat Beli Masyarakat di Kota Semarang - Yeremia Fransica Wisesa; Bambang Widjanarko Susilo; Aftuqa Sholikatur Rohmania; Wesly Tumbur ML Tobing; Galuh Aditya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of the role of promotional strategies, services, and quality of cap eucalyptus oil products on people's buying interest in the city of Semarang. The sample in this study was 100 respondents using Purposive Sampling samples and the data analysis used in this study was a multiple linear regression technique. Empirical results show that Promotion Strategy has a positive effect on product buying interest, Service has a positive effect on product buying interest, Product Quality has a positive effect on product buying interest Together Promotion Strategies, Service, and Product Quality have a positive effect on Buying Interest.